Perioperative Team Building Through Decentralization and Empowerment - Shahroch-Shahi, Paul (Operating Room Nurses Association of Canada Journal, 1995)
In our current climate of economic restraints and health care restructuring, the delivery of health care in Canada has had to be reassessed in its mode of operation and the patient care delivery system. The need for assessment, planning, implementation and evaluation of a new proactive format of health care delivery requires a creative approach for health care managers and staff nurses. Nurse managers identify decentralization as a management method of achieving job satisfaction, cost containment, and improved patient care, (Lashinger and Shamian, 1994). Staff nurses identify power sharing as a means through which nurses become empowered through the shared interaction of management in achieving a similar goal or objective within the organization. Working together these goals can result in improved patient care, cost containment and job satisfaction while fostering decentralization and the empowerment process.